The Effectiveness of Web-Based E-WoHealth on Compliance with Consumption of Iron Tablets in Young Women - Yulianti, Desak Made; Ahmad, Mardiana; Baso, Yusring Sanusi; Sinrang, Andi Wardihan; Usman, Andi Nilawati; Prihantono, Prihantono (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Utilization of technological media in the field of education and health can increase public knowledge in efforts to prevent anemia, especially in young women. One of the efforts to prevent anemia and increase adherence to taking iron tablets is by using Web-based educational media (E-WoHealth) about iron tablets supplemented with a tablet supplement consumption control card. This research aims to develop Web-based E-WoHealth media and its effect on the level of adherence to the consumption of blood supplement tablets. This study used the Research and development (R&D) method with the Borg & Gall development model and the Pre-experimental Design quantitative method using the One Group Pretest-Postest approach. The sample in this study was 80 girls in grades VII and VIII of SMP Negeri 11 Gorontalo City, determined by purposive sampling technique. Statistical tests used the McNemar test and the Chi-Square test. The results of the McNemar test showed differences in the measurement results before and after being given the Web-based E-WoHealth media with a p-value of 0.000 <0.05 meaning that the Web-based E-WoHealth media was effective in increasing adherence to consumption of iron supplement tablets (TTD) in class VII and class VIII girls and the results of the Chi-Square P-Value test were 0.822 > 0.05 meaning that there was no difference in adherence between class VII and VII girls. This study recommends the application of WEB-based E-WoHealth media equipped with an iron supplement control card to increase adherence and monitor iron supplement consumption.